Gynecological laparoscopic surgeries in the era of COVID-19 pandemic: a prospective study - Saha, Sushmita (Obstet Gynecol Sci, 2021)
OBJECTIVE: The novel coronavirus pandemic led to the suspension of elective surgeries and the diversion of resources and manpower towards pandemic control. However, gynecological emergencies and malignancies must be addressed despite the restricted resources and the need for protective measures against COVID-19. This study aimed to determine the types of gynecological surgeries performed, difficulties encountered, and their outcomes in the setting of the pandemic. METHODS: We performed a prospective cohort study over 6 months at a single tertiary center, including 60 women with gynecological complaints, categorized as emergencies and semi-emergencies, who underwent further surgery. Their surgical outcomes were measured through various parameters. RESULTS: We found that 68.3% were emergency cases, while the rest were classified as semi-emergencies. Fibroid and adenomyosis with failed medical management (48.3%), followed by cervical intraepithelial neoplasia (10%), and malignancies (10%) accounted for the semi-emergency cases, while ruptured ectopic pregnancies (13.3%) and torsion and ovarian cysts (18.4%) comprised the emergency cases. The decision to incision time between emergency and semi-emergency cases varied widely due to the safety prerequisites during the pandemic, ranging from 1 hour in emergency cases to 48 hours in semi-emergency cases. In addition, we studied the ease of preoperative preparation, patient satisfaction, and the average number of personnel available to run the operation theaters at these times. No serious perioperative adverse events were observed in the present study. CONCLUSION: In conclusion, gynecological surgeries could continue to be safely performed with all precautions in place against COVID-19 infection and related morbidities.